Against the Herd: Contrarian Investment Strategies on the Johannesburg Stock Exchange - Sarpong, Prince K. (Journal of Economics and Behavioral Studies, 2014)
This study seeks to investigate herd behaviour among equity mutual fund managers and the performance of mutual funds that trade against the herd in South Africa. The behaviour of mutual funds has an effect on the stability and volatility of stock markets, the ultimate returns to the investors. The study builds upon the efficient market hypothesis, portfolio theory and behavioural finance to provide evidence of the behaviour of mutual funds in an emerging market context using the Johannesburg Stock Exchange. The Lakonishok, Shleifer and Vishney (1991) measure of herding is used to ascertain the behaviour of mutual funds over the period 2006 to 2012. Institutional investors in South Africa are susceptible to the behavioural bias of herding and this phenomenon influences the performance of their funds. Funds that trade in the opposite direction of herd funds are able to put up a superior performance over time. Superior performance, however, does not entice mutual fund investors to invest less in under-performing funds and more in funds that recently show superior performance. These findings imply that following investment waves does not culminate in superior returns in the stock market. Consequently, mutual funds that take an opposite direction to herd funds help stabilize the stock market and lessen the severity of bear markets. This study categorizes mutual funds into ‘herding’ and ‘contrarian’ and provides an insight into the performance of each category. Investors who oppose herd behaviour realize greater returns over time while stabilizing the markets at the same time.